PENGARUH TINGKAT HARGA DAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA BISNIS RETAIL SYARIAH 212 MART (STUDI KASUS PADA 212 MART PONDOK JATI SIDOARJO) - Armas Fahmi Rizal; Ali Hamdan (ICO EDUSHA, 2021)
Study with the title "The Effect of Price Levels, and Products, on Consumer Purchase Decisions in the Sharia Retail Business of 212 Mart (Case Study At 212 Mart Pondok Jati Sidoarjo)" is a study that aims to determine whether the level of prices and products have a significant and simultaneous effect on decisions Purchase. This research is a quantitative research with data collection techniques using questionnaires and measured using a Likert scale. The population in this study were consumers at 212 Mart Pondok Jati Sidoarjo using a non-probability sampling method as many as 90 people. Furthermore, the data was analyzed using the IBM SPSS Statistics 16 application. The results of this study partially the two independent variables Price Level have t count > t table that is 4,895 > t table 1,987 and the value of Sig. 0.00. So it can be said that the product variable has a significant effect on purchasing decisions. The product variable has t count > t table which is 2.418 > 1.987 and the value of Sig. 0.018. So it can be said that the Product variable affects the Purchase Decision. Then simultaneously variable Price Level and Product also affect the Purchase Decision as evidenced by the value of f count > F table that is 13,353 > 3,100 and the value of Sig. 0.000. Keywords: Price Level, Product, Purchase Decision